Estimate the Best production function of the General Company for Iraqi Cement for the period (1996-2010) - عبد الحميد مناهل مصطفى; فرحان محمد نوري (Journal of Economics and Administrative Sciences, 2014)
The General Company for Iraqi Cement is regarded as one of the companies that contribute to support the Iraqi economy. It contributes to provide the material of cement which fulfils the consumer and investment need in the markets in competitive prices and not to resort to the importing of the cement from abroad. That would save a great share of the purchase parity of the poor sectors of society. The estimation of production function will contribute to putting the company. The application functions of the standard production of benefit critical to clarify the actual relationship between production & its components, & allow to clarify the importance of each element of the production, which helps in estimating the economic indicators & statistics, & draw the necessary plans for the advancement of the company, & that the analysis of production functions utilized in the prediction of pre-requisites to achieve target levels of production, as predictable production growth in the event of the production elements of knowledge, or that will be used in the production process in the future. Therefore will be analyzed best function production capacity of the General Company for Cement for the period (1996-2010), & in line with the logic of economic theory & then crossed statistical tests & standard, & then the expense of some economic indicators such as revenue size, elasticity of production, elasticity of substitution & technical competence. Thus, we found The General Company for Iraqi Cement followed the method of work condensation in carrying out work.